Structural insights into viral determinants of nematode mediated Grapevine fanleaf virus transmission. - Pascale Schellenberger (Public Library of Science (PLoS), 2011)
Many animal and plant viruses rely on vectors for their transmission from host to host. Grapevine fanleaf virus (GFLV), a picorna-like virus from plants, is transmitted specifically by the ectoparasitic nematode Xiphinema index. The icosahedral capsid of GFLV, which consists of 60 identical coat protein subunits (CP), carries the determinants of this specificity. Here, we provide novel insight into GFLV transmission by nematodes through a comparative structural and functional analysis of two GFLV variants. We isolated a mutant GFLV strain (GFLV-TD) poorly transmissible by nematodes, and showed that the transmission defect is due to a glycine to aspartate mutation at position 297 (Gly297Asp) in the CP. We next determined the crystal structures of the wild-type GFLV strain F13 at 3.0 Å and of GFLV-TD at 2.7 Å resolution. The Gly297Asp mutation mapped to an exposed loop at the outer surface of the capsid and did not affect the conformation of the assembled capsid, nor of individual CP molecules. The loop is part of a positively charged pocket that includes a previously identified determinant of transmission. We propose that this pocket is a ligand-binding site with essential function in GFLV transmission by X. index. Our data suggest that perturbation of the electrostatic landscape of this pocket affects the interaction of the virion with specific receptors of the nematode's feeding apparatus, and thereby severely diminishes its transmission efficiency. These data provide a first structural insight into the interactions between a plant virus and a nematode vector.